Da máquina à nuvem: caminhos para o acesso à justiça pela via de direitos dos motoristas da Uber - Ana Carolina Reis Paes Leme (2018)
This paper aims to find legitimate and adequate ways to solve conflicts in the era of electronic labor intermediation, especially among drivers hired by Uber. The research carried out in this dissertation involved the monitoring of the investigative procedure instituted by the Brazilian Public Prosecutor's Office, concerning possible injuries to the workers' collective rights, as well as to the legal order. The present dissertation also aims to demonstrate the strategies used by the company researched to seduce consumers, clients, workers and even the Government and the Judiciary, which makes it difficult, not to say unfeasible, to effectively access drivers to Justice and labor rights.